Development of a Decision Support System for Product Pricing in Small Businesses - มิ่งโมรี, สุทธดา; เจ๊ะสุ, วายีดา; พูลเพิ่ม, พุทธชาด; ปานสุวรรณ, ดุสิตา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to 1) develop a decision support system for product pricing for small businesses, 2) evaluate the system efficiency in terms of accuracy and its ability to support pricing decisions, and 3) assess user satisfaction with the developed system. The sample group consisted of 30 small business owners or entrepreneurs who sell products and determine their own pricing, selected using purposive sampling. The research instruments included: 1) a prototype decision support system for product pricing capable of calculating costs, analyzing profit, and recommending appropriate price ranges, 2) a system efficiency evaluation form completed by experts, and 3) a user satisfaction questionnaire. Data were analyzed using descriptive statistics, including mean and standard deviation.           The results showed that the overall system efficiency evaluation by experts was at a high level (x̄= 4.15, S.D. = 0.62), and the overall user satisfaction was also at a high level (x̄= 4.40, S.D. = 0.75). These findings indicate that the developed system is accurate, appropriate, and effective in supporting pricing decisions for small businesses. Furthermore, the system can be practically applied to support real-world business operations.